Using Palm Oil Waste as a Solution to Suppress Ganoderma Disease - Harefa, Taslim; Lubis, Yusniar; Martial, Tri (International Journal of Aquatic Research and Environmental Studies, 2026)
Land expansion and intensive agricultural practices trigger environmental challenges, such as land conversion and reduced soil quality due to dependence on chemical fertilizers. In addition, Ganoderma disease attacks are increasing, reducing farmers' production and income. This research aims to use palm oil waste to suppress Genoderma disease on the PT Padasa Enam Utama plantation. The method used in this research includes the ISM model approach used as an analysis of supporting policies for managing factory waste into organic fertilizer. Measurements were made on changes in soil fertility and the level of Ganoderma attacks. The research results show that the application of organic fertilizer from palm oil mill waste significantly improves soil quality, characterized by an increase in organic matter content and the activity of soil microorganisms. In addition, this treatment succeeded in reducing the level of Ganoderma attacks by up to 40%, as well as increasing production yields by 15% compared to conventional methods. Other factors, such as the availability of green open land, organizational structure, and shared stakeholder perceptions, also play an important role in supporting sustainability and circular economy practices, resulting in environmentally friendly and sustainable plantation management.
Keywords: Palm oil waste, solutions, suppressing disease, Genoderma